2009
DOI: 10.2109/jcersj2.117.475
|View full text |Cite
|
Sign up to set email alerts
|

Interface structure and polarity of GaN/ZnO heterostructure

Abstract: Gallium nitride (GaN) films were grown with and without lattice-matched (In,Ga)N buffer layers on the c(+) and c(-) faces of ZnO single-crystal substrates using molecular beam epitaxy, and their interface structures, including the relationship between the crystallinity of the GaN film and the polarity of the ZnO substrate, were investigated. Growth at a high temperature (e.g., 800°C) was made possible by using an (In,Ga)N buffer layer, which improved the crystallinity of the GaN films compared with that of GaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…As the primary reason for the high defect densities observed despite nominal lattice matching, several researchers identified the high chemical reactivity of the group-III metals with ZnO which results in a severe degradation of the interface between these two materials. [9][10][11][12] We have recently found that within a narrow temperature range, InN films of comparatively high structural quality can be synthesized on O-face ZnOð000 1Þ despite the large lattice mismatch between these two materials. 11 To investigate if such a growth window also exists when adding Ga, we compare the structural properties of thin InN and In 0:95 Ga 0:05 N films directly grown on ZnOð000 1Þ at different substrate temperatures.…”
mentioning
confidence: 99%
“…As the primary reason for the high defect densities observed despite nominal lattice matching, several researchers identified the high chemical reactivity of the group-III metals with ZnO which results in a severe degradation of the interface between these two materials. [9][10][11][12] We have recently found that within a narrow temperature range, InN films of comparatively high structural quality can be synthesized on O-face ZnOð000 1Þ despite the large lattice mismatch between these two materials. 11 To investigate if such a growth window also exists when adding Ga, we compare the structural properties of thin InN and In 0:95 Ga 0:05 N films directly grown on ZnOð000 1Þ at different substrate temperatures.…”
mentioning
confidence: 99%